The Importance and Meaningfulness of Visuals: The Situation for University Students - Ekerim, Melike G.; Yilmaz, M. Betul (PEGEM AKAD YAYINCILIK EGITIM DANISMANLIK HIZMETLERI TIC LTD STI, 2022)
The intense use of visual communication tools in today's knowledge and communication era does not mean that visual messages are correctly perceived and communication is appropriately structured. Similarly, it is just an assumption that people from younger generations, who are believed to have high levels of visual literacy, properly perceive the visuals they are exposed to. This study aims to determine whether there is a correlation between university students' visual literacy levels and their skills for comprehending, interpreting, and evaluating visuals as well as between their visual literacy perceptions of themselves and their inclination to visuals and/or text on a web page they visit. More specifically, the study examines whether university students who perceive themselves as individuals with high levels of visual literacy are really equipped with these skills and whether they incline to visuals first or not when they access a web page. In the first phase of the study, which uses a relational survey model, 478 university students were determined as subjects with the stratified sampling method, 'I he second phase was conducted with seven students determined from among the initial sample with the purposeful sampling method. The data for the study was collected with the Visual Literacy Scale developed for university students by Asian and Nalinci (2014), the Scale for Inclination to Visuals and / or Text on a Web Page, and the Performance Test for Comprehending, Interpreting and Evaluating Visuals. For statistical analysis of the study, normality analysis, exploratory factor analysis and independent groups t-test were used. The findings of the study showed that university students cannot always correctly interpret visuals although they perceive themselves as visually literate individuals. The study also revealed that university students with high levels of visual literacy perception do not recognize visuals first on a web page; however, as their visual literacy levels decrease, they preferably incline to the use of text together with visuals on a web page.
Keywords: Higher education; Tertiary students; Visual literacy; Visual preferences; INFORMATION; LITERACY; Education & Educational Research